Financial Performance Analysis Of Uluway Village In Mengkendek Sub-District, Tana Toraja Regency For The 2018-2022 Period - Tri Putri Amalia Paembonan; Andi Rustam; Nasrullah Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is a descriptive quantitative type of research with the aim of analyzing the financial performance of Uluway Village, Kec. Mentengkan District. Tana Toraja. The sample used is financial report data for the Uluway village, subdistrict. Mengkedek District, Tana Toraja in 2018-2022. Data collection is carried out by observation and requesting financial reports. In this research, the data source used in data collection is secondary data. Research result The performance of the Uluway Village Government when viewed from the Regional Financial Independence Ratio during 2018-2022, can generally be said to be very low and includes an instructive relationship pattern. Based on the Regional Original Income Effectiveness Ratio during 2018-2022, in general, it can be said to be effective. Based on the Shopping Efficiency Ratio during 2018-2022, generally, it can be considered inefficient. If we look at the PADes Growth Ratio and Total Income Growth Ratio during 2018-2022, in general, it can be said that the PADes growth ratio and total income of Uluway Village is low. If we look at the Operating Expenditure Ratio, it is classified as quite good and the average value of the capital expenditure ratio is in the good category. This means that the Uluway Village Government in allocating its funds for capital expenditure is relatively good. This shows that the village government has paid attention to the use of its funds for village development